Mechanism of exogenous methyl jasmonate in regulating the quality of fresh-cut Chinese water chestnuts - Lu, Keyan; Wu, Xinping; Yuan, Ruimin; Yi, Yang; Wang, Limei; Ai, Youwei; Wang, Hongxun; Min, Ting (Frontiers in Plant Science, 2024)
Fresh-cut Chinese water chestnuts (CWCs) are susceptible to yellowing and browning during storage due to mechanical damage and the loss of protective outer skin, adversely affecting their marketability and shelf life. Methyl jasmonate (MeJA) is currently extensively used for food preservation, but it has not been used in Chinese water chestnuts. This study investigated the effect of MeJA treatment on the quality of fresh-cut CWCs. Fresh-cut CWCs immersed in 20 μM MeJA solution for 10 min and stored at 10°C for 5 d effectively delayed the yellowing process, reduced the respiration rate, and minimized the weight and soluble solids loss during storage. In addition, MeJA treatment induced the activities of superoxide dismutase (SOD) and catalase (CAT), which improved the antioxidant capacity of fresh-cut CWCs and inhibited the generation of reactive oxygen species (ROS). Meanwhile, MeJA treatment inhibited the activities of phenylalanine aminotransferase (PAL), polyphenol oxidase (PPO) and peroxidase (POD). The results of quantitative real-time PCR (qRT-PCR) showed that MeJA downregulated the expression of CwCHS1, CwCHS2, CwCHS3 and CwCHI2 in freshly cut CWCs and inhibited the accumulation of flavonoids, thus delaying the surface discoloration of freshly cut CWCs.